The role of narrow-band imaging (NBI) endoscopy in optical biopsy of vocal cord leukoplakia - Staníková, L; Šatanková, J; Kučová, H; Walderová, R; Zeleník, K; Komínek, Pavel (European archives of oto-rhino-laryngology, 2017)
The aim of this study was to investigate whether observing microvascular changes by narrow-band imaging (NBI) endoscopy in the area surrounding leukoplakia is sufficient for discriminating between benign and malignant patterns of vocal cord leukoplakia. A total of 282 patients were investigated using white-light high-definition TV laryngoscopy and NBI endoscopy from 6/2013 to 8/2015, and 63 patients with a primary case of laryngeal leukoplakia were enrolled. Patients were divided into two groups based on leukoplakia with surrounding malignant intraepithelial papillary capillary loops (group I; 26/63) and leukoplakia with a surrounding benign vascular network (group II; 37/63), both by NBI endoscopy. All 63 patients were evaluated by blinded histological examination, and results were compared with NBI optical biopsy. Carcinoma in situ or invasive squamous cell carcinoma was confirmed in 22/26 cases (84.6 %) in group I. Hyperkeratosis or low-grade dysplasia was confirmed histologically in 31/37 (83.8 %) and squamous cell carcinoma in 2/37 (5.4 %) cases in group II. Accordance of NBI endoscopy and histopathological features of vocal cord leukoplakia lesions was statistically significant (kappa index 0.77, p < 0.001), with a sensitivity of 88.0 % (95 % CI 67.8-97.5 %) and specificity of 89.5 % (95 % CI 71.2-97.1 %). NBI is convenient for improving evaluation of laryngeal leukoplakias based on optic prehistological diagnosis. The close accordance between NBI features and histological results suggests that a negative NBI endoscopy may be an indication for long-term endoscopy follow-up without histological evaluation.
Keywords: Precancerous lesion; laryngoskopie; Endoscopy; leukoplakie; biopsie; Adult; senioři; senzitivita a specificita; Aged; Male; lidé; Carcinoma, Squamous Cell; lidé středního věku; nádory hrtanu; úzkopásmové zobrazení; Humans; Narrow Band Imaging; Hyperplasia; Vocal Cords; Middle Aged; Carcinoma in Situ; hlasové řasy; Sensitivity and Specificity; senioři nad 80 let; Narrow-band imaging; Aged, 80 and over; Laryngoscopy; mužské pohlaví; dospělí; Biopsy; hyperplazie; spinocelulární karcinom; Squamous cell carcinoma of larynx; ženské pohlaví; Female; endoskopie; karcinom in situ; Laryngeal Neoplasms; Leukoplakia